Reservoir architecture and heterogeneity distribution in floodplain sandstones: Key features in outcrop, core and wireline logs - Yeste, Luis Miguel (2020)
Exploration and production from formations deposited in low-gradient fluvial systems is typically associated with a high degree of uncertainty; a reflection of the inherent characteristics of these environments, notably the dominance of non-reservoir floodplain fines, rapid lateral facies variations and associated heterogeneities at different scales. However, for a field development to be successful it becomes crucial to know the location, geometry, dimensions and connectivity of the most permeable facies, related to the main channel and the associated proximal overbank deposits (crevasse-splay complexes). With the aim of addressing this problem, a multi-disciplinary study is presented, combining outcrop data, high-resolution sedimentological descriptions and advanced visualization techniques based on Digital Outcrop Models. This is compared with subsurface data from behind the outcrop (core, gamma ray and borehole image logs). The Mudstone–Sandstone Unit of the Triassic Red Beds of Iberian Meseta formation in south-central Spain was selected for the present study. The unit is characterized by the lateral and vertical stacking of four architectural elements: (i) channelized sandstone bodies; (ii) asymmetrical sigmoidal-shaped sandstone bodies; (iii) lobe-shaped to sheet-like sandstone bodies; and (iv) sheet-like mudstones. These elements represent meandering channel, crevasse-channel-splay and floodplain sub-environments, comprising a distal, low-gradient meandering fluvial system. Together with well-documented outcrop and core facies, calibrated log responses are also presented for the channel bodies (bell-shape Gamma Ray profile, random azimuths and low to high dip angles), the crevasse-splay bodies (funnel-shape Gamma Ray profile, unidirectional azimuths and low dip angles) and the floodplain deposits (serrated Gamma Ray profile, unidirectional azimuths and very low dip angles). The full integration of outcrop and subsurface datasets has enabled generation of a robust conceptual model with predictive potential when establishing the three-dimensional stacking of facies, distribution of heterogeneities, and the connectivity between reservoir rock geobodies of primary (channel) and secondary (crevasse complex) interest in this type of fluvial reservoir.